Boundary value problem for the heat equation with a load as the Riemann-Liouville fractional derivative - A.V. Pskhu; M.T. Kosmakova; D.M. Akhmanova; L.Zh. Kassymova; A.A. Assetov (Қарағанды университетінің хабаршысы. Математика сериясы, 2022)
A boundary value problem for a fractionally loaded heat equation is considered in the first quadrant. The loaded term has the form of the Riemann-Liouville’s fractional derivative with respect to the time variable, and the order of the derivative in the loaded term is less than the order of the differential part. The study is based on reducing the boundary value problem to a Volterra integral equation. The kernel of the obtained integral equation contains a special function, namely, the Wright function. The kernel is estimated, and the conditions for the unique solvability of the integral equation are obtained.